Ji qing shao nian kan de xue ba bi ji fa - Ishii, Takashi, 1973-; Shang, Qian (Beijing : Taiwan Strait Publishing House, 2022)
This book explains to readers how to take notes correctly. The main contents include: why to take notes, using A4 loose-leaf books and A5 notebooks at the same time, note-taking skills in class, note-taking skills to quickly improve grades, etc.
In Chinese. Translated from the Japanese
Keywords: Study skills; Learning strategies